STRUCTURE OF ACTANT IN CINDERELLA AND DATUKALINDIDI’ SOLA PUDUKBALENGKARE - Dwi Adi Nugroho; Alfiah Pratiwi; Waode Surya Darmadali (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
This research aims to describe the structure of events in Cinderella and Datukalindidi’ sola Pudu’balingkare, to outline the form of the actantial structure and functional model in these fairy tales.The researcher used structural narratology approach and descriptive method. This research is a descriptive qualitative research. In the analysis, the actant structure and functional model in these folktales had been analyzed through the actions of the characters in the story.The research result shows that not all fairy tales have a complex structure as stated in theory. Not all stages fulfilled properly. It means a lot of characters that are not one hundred percent involved in one function. However, that is exactly what become evident that the conflict character was prominent because they have dual role.